SEXY KILLERS : FILM AND ENVIRONMENTAL MOVEMENT - Murfianti, Fitri (Seni Media Rekam ISI Surakarta, 2020)
This study focuses on how a documentary film entitled Sexy Killers can be part of the campaign for change. This film with the issue of environmental damage is interesting to study about the reading of the text by the audience as an active producer of meaning. In order to understand how the audience read the text, a Sexy Killers research was conducted using a Descriptive Qualitative approach. The data collection technique used Purposive Sampling with In-Depth Interviews, then the data were processed by Content Analysis. The results of this study indicate that there are different perspectives in reading this film, which can be categorized into anthropocentrism, biocentrism and eco-centrism. This differences in reading are influenced by differences in educational backgrounds, professions, and also interests. Film as a text, is not a unit, but rather a kind of battlefield to compete to accept, reject, or negotiate certain ideas. Understanding the results of this reading can be useful for determining the right steps in encouraging the environmental conservation movement